Arabinoxylan-Oligosaccharides Act as Damage Associated Molecular Patterns in Plants Regulating Disease Resistance - Mélida, Hugo; Bacete, Laura; Ruprecht, Colin; Rebaque, Diego; del Hierro, Irene; López, Gemma; Brunner, Frédéric; Pfrengle, Fabian; Molina, Antonio (Frontiers in Plant Science, 2020)
Immune responses in plants can be triggered by Damage/Microbe-Associated Molecular Patterns (DAMPs/MAMPs) upon recognition by plant Pattern Recognition Receptors (PRRs). DAMPs are signaling molecules synthesized by plants or released from host cellular structures (e.g., plant cell walls) upon pathogen infection or wounding. Despite the hypothesized important role of plant cell wall-derived DAMPs in plant-pathogen interactions, a very limited number of these DAMPs are well characterized. Recent work demonstrated that pectin-enriched cell wall fractions extracted from the cell wall mutant impaired in Arabidopsis Response Regulator 6 (arr6), that showed altered disease resistance to several pathogens, triggered more intense immune responses than those activated by similar cell wall fractions from wild-type plants. It was hypothesized that arr6 cell wall fractions could be differentially enriched in DAMPs. In this work, we describe the characterization of the previous immune-active fractions of arr6 showing the highest triggering capacities upon further fractionation by chromatographic means. These analyses pointed to a role of pentose-based oligosaccharides triggering plant immune responses. The characterization of several pentose-based oligosaccharide structures revealed that β-1,4-xylooligosaccharides of specific degrees of polymerization and carrying arabinose decorations are sensed as DAMPs by plants. Moreover, the pentasaccharide 33-α-L-arabinofuranosyl-xylotetraose (XA3XX) was found as a highly active DAMP structure triggering strong immune responses in Arabidopsis thaliana and enhancing crop disease resistance.